Effect and mechanism of Angelic Shaoyaosan mediated AMPK/SIRT1 positive feedback loop to promote autophagy and regulate the systemic inflammatory response in acute pancreatitis - Sun, Peijun; Nie, Miao (Cellular and Molecular Biology, 2021)
This research was carried out to investigate the effect and mechanism of Angelic Shaoyaosan mediated AMPK/SIRT1 positive feedback loop to promote autophagy and regulate systemic inflammatory response in acute pancreatitis. In this study, the rat pancreatic acini AR42J cells were chosen as the research object, the application of hyla induced pancreatic acinar cells made model for acute pancreatitis, application of different concentrations of angelica peony spread effect on building cells, thus divided into control group, built in the module, the low concentration group, concentration and high concentration groups, determined by MTT method was applied to explore the above categories in cell proliferation, cell apoptosis was measured by flow cytometry, the expression of inflammatory factors in cell supernatant was determined by enzyme-linked immunoassay, and the expression of autophagy marker proteins LC3- ? and P62 was determined by Western-Bolt method. In order to explore the relationship between AMPK and SIRT1, immunoco-precipitation method was used to determine the interaction between AMPK and SIRT1, and dual luciferase experiment was used to explore the effect of AMPK on SIRT1. The AICAR group, BLM-275 group and negative control group were established. To explore the effect of SIRT1 on AMPK, we established SRT 1720 group, EX-527 group and control group. Direct binding between AMPK and SIRT1 should be determined by chromatin co-precipitation assay. In order to further explore the effect of AMPK/SIRT1 positive feedback loop on the systemic inflammatory response of acute pancreatitis, this study selected the medium-concentration Danggui Shaoyajiao SAN group as the control group (group C), and applied AMPK inhibitor BLM-275 and SIRT1 inhibitor EX 527 to the effect of medium-concentration Danggui Shaoyajiao SAN cells, respectively. The expression of autophagy marker proteins LC3- ? and P62 in groups A and B were determined by the Western-Bolt method. Results showed that compared with the control group, the cell survival rate, the expression of AMPK, SIRT1 and LC3-II in the model group were decreased, and the apoptosis rate of iNOS, IL-2, TNF-?, P62 and apoptosis were increased in the model group (P<0.05). the levels of iNOS, IL-2, TNF-?, P62 and cell survival rate in low, medium and high concentration groups decreased gradually, while the expressions of AMPK, SIRT1, LC3-II and cell apoptosis rate increased (P<0.05). The levels of iNOS, IL-2 and TNF-? in the three groups were gradually decreased with the increase of the concentration (P<0.05). Immunoprecipitation showed that AMPK and SIRT1 could bind to each other in cells. The double luciferase experiment indicated that the reporter gene containing the SIRT1 binding site was constructed. The luciferase activity was increased in THE AICAR group and decreased in the BLM-275 group (P<0.05). The reporter gene containing the AMPK promoter binding site was constructed. The luciferase activity in SRT1720 group was increased, while that in EX-527 group was decreased. SIRT1 could directly bind to the AMPK promoter. SIRT1 and LC3- ? protein expressions in group A were down-regulated, and P62 protein was increased (P<0.05). The protein expressions of AMPK and LC3- ? in group B were down-regulated, and the protein expression of P62 was increased (P<0.05). It concluded that AMPK can directly bind to activate SIRT1 expression, and SIRT1 expression can also activate AMPK, forming a positive feedback loop between the two. Therefore, Angelic Shaoyaodong decoction can mediate AMPK/SIRT1 positive feedback pathway to promote autophagy and regulate systemic inflammatory response in acute pancreatitis.